Internet connectivity disruption in Burundi (Burundi) - Voidly (2026)
CRITICAL severity disruption detected in Burundi. Confidence: 65%. Data sourced from IODA.
Network Disruption Incident ID: BI-2026-0011
Keywords: internet disruption; BI; disruption; critical